Dominant modifiable risk factors for stroke in Ghana and Nigeria (SIREN): a case-control study. Issue 4 (April 2018) - Owolabi, Mayowa O; Sarfo, Fred; Akinyemi, Rufus; Gebregziabher, Mulugeta; Akpa, Onoja; Akpalu, Albert; Wahab, Kolawole; Obiako, Reginald; Owolabi, Lukman; Ovbiagele, Bruce; ,; ,
Summary: Background: Sub-Saharan Africa has the highest incidence, prevalence, and fatality from stroke globally. Yet, only little information about context-specific risk factors for prioritising interventions to reduce the stroke burden in sub-Saharan Africa is available. We aimed to identify and characterise the effect of the top modifiable risk factors for stroke in sub-Saharan Africa. Methods: The Stroke Investigative Research and Educational Network (SIREN) study is a multicentre, case-control study done at 15 sites in Nigeria and Ghana. Cases were adults (aged ≥18 years) with stroke confirmed by CT or MRI. Controls were age-matched and gender-matched stroke-free adults (aged ≥18 years) recruited from the communities in catchment areas of cases. Comprehensive assessment for vascular, lifestyle, and psychosocial factors was done using standard instruments. We used conditional logistic regression to estimate odds ratios (ORs) and population-attributable risks (PARs) with 95% CIs. Findings: Between Aug 28, 2014, and June 15, 2017, we enrolled 2118 case-control pairs (1192 [56%] men) with mean ages of 59·0 years (SD 13·8) for cases and 57·8 years (13·7) for controls. 1430 (68%) had ischaemic stoke, 682 (32%) had haemorrhagic stroke, and six (<1%) had discrete ischaemic and haemorrhagic lesions. 98·2% (95% CI 97·2–99·0) of adjusted PAR of stroke was associated with 11 potentially modifiable risk factors with ORs and PARs in descending order of PAR of 19·36 (95% CI 12·11–30·93) and 90·8% (95% CI 87·9–93·7) for hypertension, 1·85 (1·44–2·38) and 35·8% (25·3–46·2) for dyslipidaemia, 1·59 (1·19–2·13) and 31·1% (13·3–48·9) for regular meat consumption, 1·48 (1·13–1·94) and 26·5% (12·9–40·2) for elevated waist-to-hip ratio, 2·58 (1·98–3·37) and 22·1% (17·8–26·4) for diabetes, 2·43 (1·81–3·26) and 18·2% (14·1–22·3) for low green leafy vegetable consumption, 1·89 (1·40–2·54) and 11·6% (6·6–16·7) for stress, 2·14 (1·34–3·43) and 5·3% (3·3–7·3) for added salt at the table, 1·65 (1·09–2·49) and 4·3% (0·6–7·9) for cardiac disease, 2·13 (1·12–4·05) and 2·4% (0·7–4·1) for physical inactivity, and 4·42 (1·75–11·16) and 2·3% (1·5–3·1) for current cigarette smoking. Ten of these factors were associated with ischaemic stroke and six with haemorrhagic stroke occurrence. Interpretation: Implementation of interventions targeting these leading risk factors at the population level should substantially curtail the burden of stroke among Africans. Funding: National Institutes of Health.